Childhood obesity in Asia : current status and future trend - Abdolreza Norouzy (Indonesian Nutrition Association, 2022)
The prevalence of overweight among all children and adolescents, from infancy to the age of 19, is on the increase worldwide. This figure for children under five years old is almost 6%, and for children 5 to 19 years, it is estimated at 18%. This results from individual factors and the creation and progression of an obesogenic environment in human societies.